MEMPENGARUHI BUDAYA ORGANISASI SERTA LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT O’O’U KAB. NISEL - Tutial Bertina Halawa (Jurnal Ekonomi dan Bisnis Nias Selatan, 2022)
The aim of this research is to identify the influence of organizational culture and work environment on employee performance at the O'o'u Regency Head Office, South Nias Regency. This research uses a quantitative association approach with data sources from employees and involves 30 respondents as samples. The data collection technique used is a research instrument or questionnaire, while the data analysis method used is multiple linear regression analysis. The research results show that organizational culture has a significant influence on employee performance, with a calculated t value of 2554 which exceeds the t table value of 1703. Likewise, the work environment also has a significant influence on employee performance, with a calculated t value of 3862 which also exceeds the t table value of 1703. Based on these findings, it can be concluded that organizational culture and work environment have a positive impact on employee performance at the O'o'u District Head Office, South Nias Regency. Therefore, several recommendations can be proposed (1) The leadership of  needs to pay further attention to organizational culture and work environment. This includes ensuring work facilities such as computers, cupboards, lights, windows and equipment to support work performance are available and functioning properly. (2) The Central Management of O'o'u South Nias Regency should continue to provide training to employees in an effort to keep them motivated and motivated in carrying out their work with high enthusiasm. (3) Employees of  also have an important role in improving their performance. They must work with enthusiasm and try to maximize the results of their work by using the abilities they have. By implementing these recommendations, it is hoped that employee performance at can be significantly improved.